Socio-familiar factors that influence in the consumption of psichoactive substances in the integrants of rehabilitation institution in the department of Quindio - Colombia - Gonzales Portillo, Juan (2017)
This research pretends identify the social family factors that influence the psychoactive substances consume in a rehab institution in the department of Quindío, in the pursuit of the objective was applied the APGAR Family instrument and a characterization chart of consume to 37 members of the institution from 18 to 55 years old, most of them was men, the average age of the consume was 11 years old, marijuana being the substance that is most consumed. This study is quantitative, descriptive and correlational, which pretends identify if the relationship between the study varia bles exists or not. The main variable on the severity of consume was the number of substances currently used by each of the participants. There were no correlation values between the test results and the consume characteristics, except in the age of begin with the leve) of family functioning and if the participants currently have family visits in the institution with the number of substances consumed, this gives traces about the relationship between the family structure as one of the variables to consider in the beginning and rehabilitation of the consume of psychoactive substances.